Transition to Virtual Graduation: Experiences of 2021 University Graduates in Zimbabwe - Namatirai Chikusvura; Sesilani Nkomo; Lwazi Sibanda (RIRAI Publisher, 2022)
The research sought to investigate graduates' experiences with the shift to virtual graduation. The interpretive paradigm used in this study aided the current researchers in maintaining the integrity of the phenomenon being investigated, which comprehends the experiences of graduates on various platforms used at graduation. Qualitative method was utilized. The research included thirty randomly chosen graduates from three different institutions. Data was gathered using a semi-structured questionnaire. According to the report, institutions focused more on physical ceremony arrangements, despite the fact that the majority of students participated digitally. The study also found that other graduates enjoyed the graduation because they attended physical virtual graduation events planned by student representatives and held at various locations. Graduates, on the other hand, were financially burdened since they had to invest additional graduation expenditures in order to attend these physical virtual graduation festivities. The study concluded that the effectiveness of various virtual graduation formats as measured by participant satisfaction, ease of access, ability to optimize social presence, and engagement was not achieved. In this aspect, the survey indicated that colleges prioritized actual graduation ceremonies over virtual ceremonies. The research suggests that colleges collaborate with various event planners to supply and host their grads, allowing all graduates to experience a feeling of connection and success.